Host Suitability of Tobacco Leaf Eating Caterpillar (Spodoptera litura F.) under Laboratory Condition - Dodiya, R. D.; Barad, A. H.; Italiya, J. V.; Pathan, N. P.; Bhatt, N. A. (International Journal of Bio-resource and Stress Management, 2023)
A study was conducted at the Bidi Tobacco Research Station, AAU, Anand laboratory during kharif (June-October 2021) to determine the most suitable host plant of S. litura among the groundnut, tobacco and castor. A statistically designed lab experiment using Completely Randomized Design (CRD) having twenty-five Repetitions and three treatments was laid out. Total life span of S. litura was longer on castor followed by groundnut and least duration was observed on tobacco. The egg hatching % was found more or less similar in each of host crop. Eggs were clustered and covered in tiny buff-colored hairs that resembled hairs on the gravid female’s abdomen tip. The total larval period from the first to sixth instar was recorded longer on castor followed by on groundnut and tobacco. Last larval instar was very active and consuming prolifically on leaves, resulting in the whole leaf being fed with just the mid rib remaining. The pupal period was found similar on three different hosts. Pupa become shiny, greenish in color after that color change from greenish to brownish yellow to light brown to dark brown in color with shiny appearance. Adult longevity of both male and female was found to be longer on castor followed by groundnut and tobacco. Adult moths (both male and female) were yellowish brown in colour, with a prominent head and black compound eyes. The female was somewhat bigger and stouter than the male. Fecundity (egg masses female-1) of adult female was noticed similarly in different host crops. Sex ratio of S. litura on groundnut was 1:1, on castor 1:1.09 and on tobacco 1:1.38.